2009
DOI: 10.1097/shk.0b013e318189017a
|View full text |Cite
|
Sign up to set email alerts
|

LOSARTAN PREVENTS SEPSIS-INDUCED ACUTE LUNG INJURY AND DECREASES ACTIVATION OF NUCLEAR FACTORκB AND MITOGEN-ACTIVATED PROTEIN KINASES

Abstract: Lack of specific and efficient therapy leads to the high mortality rate of acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). Losartan is a potent pharmaceutical drug for ALI/ARDS. However, the protective effects and mechanisms of losartan remain incompletely known. This study evaluates the effects of losartan on ALI/ARDS and further investigates the possible mechanisms of these protective effects. Mice received i.p. injections of the AT1 inhibitor losartan (15 mg/kg), or control vehicle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 29 publications
8
88
0
1
Order By: Relevance
“…Or inflammatory response activates p38MAPK? Please refer to page 12, the last paragraph) (Lentsch et al, 1998;Asaduzzaman et al, 2008;Shen et al, 2009). We proved that, in the present study, phosphorylation and consequent activation of p38MAPK and NF-κB were blocked by hydrogen-rich saline.…”
Section: Discussionsupporting
confidence: 80%
“…Or inflammatory response activates p38MAPK? Please refer to page 12, the last paragraph) (Lentsch et al, 1998;Asaduzzaman et al, 2008;Shen et al, 2009). We proved that, in the present study, phosphorylation and consequent activation of p38MAPK and NF-κB were blocked by hydrogen-rich saline.…”
Section: Discussionsupporting
confidence: 80%
“…The upper lobe of the right lung was removed 24 h after CLP, weighed, and then dried in an oven at 80 C for 48 h. The dry tissue weight was measured, and the wet-to-dry weight (w/d) ratio was calculated to evaluate the degree of lung edema [14].…”
Section: Assessments Of Lung Edemamentioning
confidence: 99%
“…We are not aware of any reports using an ARB in a mouse model of pancreatitis. IP delivery of losartan was chosen because it was shown that IP injections of losartan in mice caused biological effects such as prevention of sepsis-induced acute lung injury (35) and regulation of blood pressure (27). We Expression of angiotensinogen and AT1b mRNA is normalized to acidic ribosomal phosphoprotein P0 and expressed as fold increase over the level in WT control mice.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate whether simultaneous blockade of AT1a and AT1b receptor isoforms affects the course of cerulein-induced pancreatitis, WT cerulein-treated mice (8 mice/group) were treated with AT1 receptor antagonist losartan and compared with control cerulein-treated mice (8 mice/group). Losartan was delivered by IP injection because it was demonstrated in several studies that IP delivery of losartan produces biological effects in mice (27,35). Several doses of losartan, 0.5 mg/kg per day, 2 mg/kg per day, 5 mg/kg per day, and 20 mg/kg per day were evaluated.…”
Section: Expression Of At1a and At1b Mrna In The Pancreasmentioning
confidence: 99%